Current Problems in Dermatology 2006
DOI: 10.1159/000093940
|View full text |Cite
|
Sign up to set email alerts
|

Use of Textiles in Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease which usually starts during the first years of life. In the management of AD, the correct approach requires a combination of multiple treatments to identify and eliminate trigger factors, and to improve the alteration of the skin barrier. In this article we try to explain the importance of skin care in the management of AD in relation to the use of textiles: they may be useful to improve disrupted skin but they are also a possible cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
0
46
0
Order By: Relevance
“…83 Treated textiles have been evaluated in clinical studies as part of a treatment strategy for atopic dermatitis for several years. [84][85][86] More recent research is targeting the general infection prevention market. Antimicrobial agents for textiles represent a diverse array of chemicals and metals including but not limited to gold, silver, copper, chitosan, chitooligosaccharides, quaternary ammonium compounds, and zeolite-containing compounds.…”
Section: Outbreaks Of Infection Attributed To Laundered Hctsmentioning
confidence: 99%
“…83 Treated textiles have been evaluated in clinical studies as part of a treatment strategy for atopic dermatitis for several years. [84][85][86] More recent research is targeting the general infection prevention market. Antimicrobial agents for textiles represent a diverse array of chemicals and metals including but not limited to gold, silver, copper, chitosan, chitooligosaccharides, quaternary ammonium compounds, and zeolite-containing compounds.…”
Section: Outbreaks Of Infection Attributed To Laundered Hctsmentioning
confidence: 99%
“…Itch can be elicited by innocuous touching of normal skin around a site of histamine-evoked itch (Bickford, 1937; Graham et al, 1951; Heyer et al, 1997; Simone et al, 1991). In chronic itch patients low-threshold mechanical stimuli, such as clothes contacting the skin, can initiate the itch-scratch cycle (Bendsoe et al, 1987; Heyer & Hornstein, 1999; Mason, 2008; Ricci et al, 2006; Wahlgren, 1991). …”
Section: Introductionmentioning
confidence: 99%
“…In this double-blind, placebo-controlled trial with 68 atopic dermatitis patients, they were able to show that antimicrobial fabrics, worn for 2 weeks tightly on the skin, may reduce the nonphysiological colonization of the patients skin with the microorganism Staphylococcus aureus [4, 5]. Subsequently similar studies confirmed that antimicrobial cloth at least have influence on the pathological skin flora of atopic dermatitis skin and thus may support or reconstitute physiological functions [68]. Whether an influence on the physiological skin flora on skin of healthy subjects occurs has not been addressed so far.…”
Section: Introductionmentioning
confidence: 99%